1994
DOI: 10.1161/01.str.25.4.864
|View full text |Cite
|
Sign up to set email alerts
|

The role of superoxide anions in the pathogenesis of cerebral vasospasm.

Abstract: To determine the role of superoxide anions in the pathogenesis of cerebral vasospasm after aneurysmal subarachnoid hemorrhage, we studied the preventive effect of human recombinant copper-zinc superoxide dismutase (h-r SOD) in a rabbit subarachnoid hemorrhage (SAH) model. Forty-five rabbits receiving intracisternal injection of 3 mL autologous nonheparinized blood or 3 mL saline were divided into four groups as follows: (1) saline injected and no treatment (control group, n = 6); (2) blood injected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 29 publications
(22 reference statements)
0
37
1
Order By: Relevance
“…Human recombinant Cu-Zn SOD has been found to prevent VS at 2 -4 days in a rabbit SAH model and to prevent the appearance of endothelial lesions (236). In a cisternal talc injection model which induced strong VS at 3 -7 days, it was found that SOD significantly inhibited the VS and almost abolished the associated myonecrosis and cell junction detachment (237).…”
Section: -1 Superoxide Radical Scavengersmentioning
confidence: 99%
“…Human recombinant Cu-Zn SOD has been found to prevent VS at 2 -4 days in a rabbit SAH model and to prevent the appearance of endothelial lesions (236). In a cisternal talc injection model which induced strong VS at 3 -7 days, it was found that SOD significantly inhibited the VS and almost abolished the associated myonecrosis and cell junction detachment (237).…”
Section: -1 Superoxide Radical Scavengersmentioning
confidence: 99%
“…Considering that free radicals or cytokines are associated with the pathogenesis of cerebral vasospasm after SAH, 31,32 part of the mechanisms of vasospasm might be mediated by the activation of MAPK. Gerthoffer et al 7 and Hedges et al 8 have speculated that MAPK activation mediates cerebral vasospasm because MAPK activation induces the phosphorylation of caldesmon that, in turn, leads to vascular smooth muscle contraction.…”
Section: Mechanism Of Mapk Activation During Vasospasmmentioning
confidence: 99%
“…5,6 In support of the theory that ROS are primary pathogens for SAH, a variety of antioxidants have been shown to attenuate cerebral vasospasm in animals and humans. [7][8][9][10][11][12][13][14] We have shown that intracisternal overproduction of ⅐O 2 Ϫ may initiate and/or mediate cerebral arterial vasoconstriction and subsequent structural damage. 3 Moreover, administration of ferrous (Fe 2ϩ ) or ferric (Fe 3ϩ ) iron chelators was shown to mitigate against cerebral vasospasm, providing evidence that the iron-catalyzed Haber-Weiss and Fenton reactions are involved in the mechanism of ROS generation leading to the occurrence of cerebral vasospasm.…”
mentioning
confidence: 99%